2020
DOI: 10.9734/jamps/2020/v22i130153
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Clinical Profiles of Cannabis Abusers Admitted for Treatment in a Tertiary Healthcare Facility in Uyo, South-South Nigeria

Abstract: Background: Cannabis is one of the commonly abused psychoactive substances worldwide. The increasing abuse of this psychoactive substance is recognized as a significant public health problem in many developing countries. A proper assessment of the patterns and trends of cannabis use disorders will be useful because of the increasing number of cannabis abusers worldwide and demand for appropriate treatment. Aims: This study examined the socio-demographic and clinical characteristics of cannabis abusers admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
2
2
0
Order By: Relevance
“… 27 However, in a study conducted at a tertiary treatment facility for drug abusers, the mean age reported was closer to our finding. 28 The same study by Effiong et al also reported the mean age at the onset of smoking, which fell within the modal class for the age at smoking onset found in our study.…”
Section: Discussionsupporting
confidence: 89%
“… 27 However, in a study conducted at a tertiary treatment facility for drug abusers, the mean age reported was closer to our finding. 28 The same study by Effiong et al also reported the mean age at the onset of smoking, which fell within the modal class for the age at smoking onset found in our study.…”
Section: Discussionsupporting
confidence: 89%
“…These researchers reported that males abuse drugs due to idleness, lack of stable job and source of livelihood. This validates the assertion of Effiong et al (2020) that cannabis users are mostly unemployed single young males. The zeal to kill emotional pain; lack of confidence to say no to friends; the need to feel strong and manly among others were additional reasons why men engage in drug use.…”
Section: Introductionsupporting
confidence: 89%
“…Balogun et al (2020) though conducted in Nigeria differs from the present study in that it utilizes only descriptive but not inferential statistics in determining its results. The study however differs from Effiong et al, (2020) in the area of the focus and statistics use. While Effiong et al (2020) attentions were on sociodemographic and clinical characteristics of cannabis abusers, the present study concentrate on senior school students' knowledge on drug abuse and addiction.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation